Xenogeneic-Free System for Biomanufacturing of Cardiomyocyte Progeny From Human Pluripotent Stem Cells - Ashok, Preeti; Parikh, Abhirath; Du, Chuang; Tzanakakis, Emmanuel S. (Frontiers in Bioengineering and Biotechnology, 2020)
Functional heart cells and tissues sourced from human pluripotent stem cells (hPSC) have great potential for substantially advancing treatments of cardiovascular maladies. Realization of this potential will require the development of cost-effective and tunable bioprocesses for manufacturing hPSC-based cell therapeutics. Here, we report the development of a xeno-free platform for guiding the cardiogenic commitment of hPSCs. The system is based on a fully defined, open-source formulation without complex supplements, which have varied and often undetermined effects on stem cell physiology. The formulation was used to systematically investigate factors inducing the efficient commitment to cardiac mesoderm of three hPSC lines. Contractile clusters of cells appeared within a week of differentiation in planar cultures and by day 13 over 80% of the cells expressed cardiac progeny markers such as TNNT2. In conjunction with expansion, this differentiation strategy was employed in stirred-suspension cultures of hPSCs. Scalable differentiation resulted in 0.4-2 million CMs/ml or ~5-20 TNNT2-positive cells per seeded hPSC without further enrichment. Our findings will contribute to the engineering of bioprocesses advancing the manufacturing of stem cell-based therapeutics for heart diseases.